Accurate Tongue–Palate Pressure Sensing Device to Study Speech Production and Swallowing in Patients with Complete Denture - Mirchandani, Bharat; Perrier, Pascal; Grosgogeat, Brigitte; Jeannin, Christophe (European Journal of Dentistry, 2021)
Objectives The mechanical interactions between tongue and palate are crucial for speech production and swallowing. In this study, we presented examples of pressure signals that can be recorded with our PRESLA system (PRESLA holds for the French expression “PRESsion de la LAngue” [Pressure from the tongue]) to assess these motor functions, and we illustrate which issues can be tackled with such a system.Materials and Methods A single French-speaking edentulous subject, old wearer of a complete denture, with no speech production and swallowing disorders, was recorded during the production of nonsense words including French alveolar fricatives, and during dry and water swallowing. The PRESLA system used strain-gauge transducers that were inserted into holes drilled in the palatal surface of a duplicate of the prosthesis at six locations that were relevant for speech production and swallowing. Pressure signals were postsynchronized with the motor tasks based on audio signals.Results Patterns of temporal variations of the pressure exerted by the tongue on the palate are shown for the two studied motor tasks. It is shown for our single subject that patterns for fricative /s/ are essentially bell shaped, whereas pressure signals observed for water swallow begin with a maximum followed by a slow decrease during the rest of the positive pressure phase. Pressure magnitude is almost 20 times larger for water swallow than for /s/ production.Conclusions This study illustrates the usefulness of our PRESLA system for studying speech production and swallowing motor control under normal and pathological conditions.
Keywords: tongue–palate interactions; complete denture; speech production; swallowing; strain–gauge sensors